Business Coaching Method to Increase Student’s Passion in Basic Accounting Phase E Vocational School - Sohidin Sohidin; Sri Sumaryati (Universitas Negeri Semarang, 2025)
The aim of this research is to examine the effectiveness of the business coaching method in enhancing student interest and understanding in Basic Accounting subjects within the independent curriculum. Specifically, this study aims to: (1) assess the extent to which the business coaching method increases student interest in Basic Accounting Phase E, and (2) analyze differences in student conditions before and after the implementation of the business coaching method in the classroom. This study employs an experimental method with structured stages and an independent t-test for data analysis. The research sample consists of control and experimental groups from Class X students at State Vocational School 1 Boyolali, Central Java. The findings indicate that the application of the business coaching method significantly impacts students' understanding of financial reports in Basic Accounting, demonstrating its effectiveness in making learning more interactive, engaging, and conducive to creative thinking and collaboration.